Perancangan dan Pengujian Kinerja Expert Advisor Berbasis Indikator RSI, MA, dan Optimasi Lot pada 10 Pair Forex Populer dengan Akun Swap-Free - Nasution, Mutiara Akbar (Jurnal Sains, Teknologi & Komputer, 2024)
This study aims to test the performance of an Expert Advisor (EA) based on the Relative Strength Index (RSI), Moving Average (MA), and lot optimization on 10 popular forex pairs using a swap-free account. The EA is designed to operate on the MetaTrader 5 platform, utilizing historical data from 2021 to 2024. The study employs a backtesting method to assess EA effectiveness across various market conditions. Results indicate that the EA performs best on lower volatility pairs, such as USDCAD and GBPUSD, showing positive profitability and controlled risk ratios. However, suboptimal performance is observed on high-volatile pairs such as GBPJPY and EURJPY. These findings highlight the importance of tailoring EA strategies to pair volatility characteristics to enhance profitability and risk management.